2020
DOI: 10.1016/j.sleh.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination as a mediator of racial disparities in insomnia disorder

Abstract: Study Objectives Racial and ethnic minorities are more likely to suffer from insomnia that is more severe; however, few studies have examined mechanisms by which racial disparities in severity of insomnia disorder may arise. One potential mechanism for disparities in insomnia severity is perceived discrimination. This study tested discrimination as a mediator in the relationship between race and insomnia. Methods Participants were recruited from communities in the Detro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 76 publications
(96 reference statements)
2
23
0
Order By: Relevance
“…This finding is especially notable as no significant racial differences in insomnia severity were found in the same sample prior to the pandemic after receiving insomnia treatment in 2016/2017. Furthermore, the Black-White disparity in insomnia severity during the pandemic in this sample was approximately threefold the magnitude of disparities found pre-pandemic [ 17 , 68 ], suggesting that the racial disparities in insomnia grew in conjunction with the disproportionate social stressors during the pandemic. Results also indicated that Black participants reported higher levels of COVID-related stress compared to White participants, and that this stress was associated with a history of perceived racial discrimination prior to the pandemic.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This finding is especially notable as no significant racial differences in insomnia severity were found in the same sample prior to the pandemic after receiving insomnia treatment in 2016/2017. Furthermore, the Black-White disparity in insomnia severity during the pandemic in this sample was approximately threefold the magnitude of disparities found pre-pandemic [ 17 , 68 ], suggesting that the racial disparities in insomnia grew in conjunction with the disproportionate social stressors during the pandemic. Results also indicated that Black participants reported higher levels of COVID-related stress compared to White participants, and that this stress was associated with a history of perceived racial discrimination prior to the pandemic.…”
Section: Discussionmentioning
confidence: 78%
“…social isolation from quarantine) may further exacerbate pre-existing disparities (e.g. reduced sense of belonging due to racial discrimination) that then widen the racial disparity in insomnia severity during the pandemic [ 23 , 24 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to this call, the articles in this virtual special issue have explored a range of social experiences that have characterized racialized identities in the U.S: essential worker status during the COVID-19 pandemic 26 ; lower socioeconomic status 27 28 ; and experiences of racial discrimination. 29 , 30 It is imperative that research continues to evolve beyond comparisons of racial-ethnic groups on sleep and other health outcomes, and instead focus on explaining the unique processes that characterize experiences among diverse groups of individuals. The finding of opposite educational gradients in sleep duration between Black and White adults 31 illustrates the need to retire a “one size fits all” approach and turn, instead, toward understanding the unique barriers and challenges that specific groups of individuals face in their quest for adequate, restorative sleep.…”
Section: Key Contributions Of the Virtual Special Issuementioning
confidence: 99%
“…51 Racial discrimination has also been shown to be a significant mediator of the relationship between race and insomnia symptom severity. 52 Another study found that among women, those who identify as Black/African American, Asian/Other, or Hispanic/Latino were significantly less likely than their white counterparts to have sleep complaints, while racial differences were not apparent among men; the authors posited that it may be that non-white women may be less likely to complain about their sleep. 53…”
Section: Sex and Insomniamentioning
confidence: 99%